1998
DOI: 10.1016/s0886-3350(98)80048-5
|View full text |Cite
|
Sign up to set email alerts
|

Secondary implantation of scleral-fixated intraocular lenses

Abstract: Secondary IOL implantation with scleral fixation was a safe procedure. Although there was a small risk of significant complications, more than 90% of patients regained or improved their preoperative visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 36 publications
4
61
0
4
Order By: Relevance
“…[9][10][11][12][13][14] The retinal detachment rate in this study is comparable to the rate of 3.2% found in a previous study in eyes that underwent complete pars plana vitrectomy at the time of SPCIOL implantation. 8 Comparison of these two series may, however, be misleading, the previous series being largely eyes with uncomplicated ectopia lentis or aphakia following trauma unlike the more heterogeneous aetiology of aphakia in the current study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[9][10][11][12][13][14] The retinal detachment rate in this study is comparable to the rate of 3.2% found in a previous study in eyes that underwent complete pars plana vitrectomy at the time of SPCIOL implantation. 8 Comparison of these two series may, however, be misleading, the previous series being largely eyes with uncomplicated ectopia lentis or aphakia following trauma unlike the more heterogeneous aetiology of aphakia in the current study.…”
Section: Discussionsupporting
confidence: 87%
“…All three eyes had no light perception at final follow-up. In the reports of SPCIOL implantation where the outcome of retinal detachment was included, [8][9][10][11]14,15 the reattachment rate was 79% (23/ 29). PVR was reported as the cause of failure in almost all cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the IOP levels were within normal limits at last follow-up in both groups. 34 Uthoff et al 35 showed suture erosion (17.9%), cystoid macular edema (5.8%), retinal detachment (1.4%), vitreous hemorrhage (1.0%), and uveitis (0.5%) in a 1-year postoperative outcome of scleral-fixated IOL. Kumar et al 28 reported that late complications were pigment dispersion (3.7%), healed macular edema (7.5%), and 5.23 ± 3.4% loss of endothelial cells, but results obtained at 1 year showed a good visual outcome, with minimal complications in eyes with deficient capsular support.…”
Section: Discussionmentioning
confidence: 98%
“…Discussion SFIOL has been used in both adults and children with success, either as a single procedure or combined with penetrating keratoplasty and other vitreoretinal procedures. 3,[8][9][10][11] There are many variations of the technique and a range of complications of varying frequencies, which include suture and knot erosions, lens tilt, dislocation or decentration, infection, glaucoma, cystoid macula oedema, corneal decompensation, retinal detachment, and suprachoroidal haemorrhage. 3,[8][9][10][11][12][13][14][15] The maintenance of ocular tension and the avoidance of globe collapse would be technically demanding in cases with low scleral rigidity, small palpebral fissures (eg oriental eyes), poor exposure, and high vitreous pressure.…”
Section: Resultsmentioning
confidence: 99%
“…3 One of the common problems encountered by surgeons performing SFIOL is the tendency for globe collapse during the procedure. The maintenance of globe integrity is particularly difficult in eyes with low scleral rigidity and small palpebral fissures (eg oriental eyes).…”
Section: Introductionmentioning
confidence: 99%